Evaluation of the Implementation of Advertising Tax Collection Policy in North Bekasi District, Bekasi City for 2020-2022 - Milleano, Dani; Dewi, Sekar Amalia; Rahmawati, Aninda; Harjo, Dwikora (Yayasan Sinergi Kawula Muda, 2023)
Bekasi city, as an autonomous region in West Java Province, holds promising potential for local revenue. Various forms of business and large industries have successfully attracted domestic and international invesments, contributing to the global trade. Due to the abudance of goods and services produced, media and advertising play a crucial role in introducing and educating consumers about these products. Advertisement tax servers as one of the key sources of local revenue. Advertisement act as a medium to disseminate information to the general public and are placed alongside roads, conveying messages and information. This research aims to evaluate the implementation of the advertisement tax collection policy in North Bekasi Sub-district, Bekasi City, from 2020 to 2022. The analytical technique employed in this study is descriptive analysis with a qualitative approach. The research findings reveal that the realization of advertisement tax in 2022 did not meet the set target, with an average result of 95.11%, categorizing the effectiveness for 2022 as moderately effective. The main hindrance lies in the lack of taxpayer awareness, and the online registration service on the website occasionally consumers time for the issuance of SKPD and advertisement permits. Efforts have been made to address this issue, including conducting socialization and monitoring activities for taxpayers.